HGG-15. PHASE 2 NESTED COHORT STUDY OF DEPATUXIZUMAB MAFODOTIN IN CHILDREN WITH HIGH GRADE GLIOMA AND DIFFUSE INTRINSIC PONTINE GLIOMA WITH EGFR AMPLIFICATION. Issue 2 (22nd June 2018) - van den Bent, Martin; Dinjens, Winand; Golfinopoulos, Vassilis; Ansell, Peter; Dungey, Fiona; de Geus, Jan Peter; Bain, Earle; Looman, Jim; Xiong, Hao; Hargrave, Darren
Abstract: INTRODUCTION: Pediatric high grade gliomas (HGGs) and diffuse intrinsic pontine gliomas have no adequate therapy and are almost universally fatal. Depatuxizumab mafodotin (depatux-m) is an antibody-drug conjugate, comprised of anti-EGFR antibody linked to a microtubule cytotoxin, monomethyl auristatin F, that has demonstrated promising antitumor activity in patients with EGFR gene-amplified tumors in two studies of adult glioblastoma. While EGFR amplification occurs in 50% of adult glioblastomas, it occurs in only 1-3% of children. Due to this rarity, a nested pediatric cohort has been designed within the adult depatux-m phase 2 study in recurrent glioblastoma (NCT02343406). METHODS: At least 6 patients will be enrolled globally. Eligible patients will be 3-17 years of age, tumors exhibiting EGFR amplification. Primary objectives include evaluating safety, tolerability, and pharmacokinetic profile. Secondary objective was to assesses tumor response per RANO criteria. To facilitate study access, we aim to analyze tumor specimens of at least 200 pediatric patients for EGFR amplification. Sites can use local or central EGFR testing. Additionally, tissue samples may also be sent to Erasmus Cancer Hospital, The Netherlands, for glioma-tailored next generation sequencing molecular panel/array, including EGFR amplification, by anyone (open to any HGG patient). Erasmus will provide these results directly to the physician. Physicians wishing to utilize this testing service (open to any patient) can contact h.dubbink@erasmusmc.nl. RESULTS: Of 98 patients pre-screened or began pre-screening: 75 were not EGFR amplified, 12 were not tested (e.g. insufficient tissue, progression), 3 are pending result, 8 are EGFR amplified, and 2 patients have been enrolled.